أثر الاستثمار الأجنبي المُباشر في النمو الاقتصادي في سورية خلال الفترة 2000-2010 - علي مدين; عمران أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
بدأ الاستثمار الأجنبي المُباشر FDI يلعب دوراً كبيراً في دعم نمو اقتصاديات الدُّول النامية منذ ثمانينات القرن الماضي، مُستفيداً من الانتشار السريع لتكنولوجيا المعلومات والاتصالات ICT والاتجاه نحو اقتصاد السوق في مُعظم الدُّول النامية وتحرير التجارة فيها، وازداد اعتماد هذه الدُّول على الاستثمار الأجنبي المُباشر نظراً للمنافع الكبيرة التي تجنيها منه، سواءً من ناحية تكوين رأس المال وتوليد العمالة وزيادة الصادرات، أو من ناحية الحصول على التكنولوجيا الحديثة اللازمة لتحقيق التنمية الاقتصادية. وفي سورية بدأت تدفُّقات الاستثمار الأجنبي المُباشر بالتزايد منذ العام 2003، وذلك نتيجة التوجُّهات الجديدة للحكومة السُّوريَّة نحو الانفتاح على القطاع الخاص المحلي والأجنبي والاعتماد على اقتصاد السوق. هدَفَ هذا البحث إلى تسليط الضوء على واقع الاستثمار الأجنبي المُباشر في سورية، وتوضيح أثر هذا الاستثمار في النمو الاقتصادي خلال الفترة 2000-2010، وقد توصَّل البحث إلى أنَّ هذا التأثير كان ضعيفاً. Foreign direct investment FDI has been started to play a major role in supporting the growth of the economies of developing countries since the eighties of the last century, taking advantage of the rapid spread of information and communication technology ICT and the trend towards a market economy in most developing countries and trade liberalization in them. These countries began to depend more on foreign direct investment because of the great benefits that derive from it in terms of capital, employment and increase in exports, or in terms of obtaining the modern technology which is necessary to achieve the economic development. In Syria, foreign direct investment flows started to increase since 2003 as a result of the new directions of the Syrian government to open up to domestic and foreign private sector, and reliance on the market economy. The objective of this research is to shed light on the reality of foreign direct investment in Syria, and to clarify the impact of this investment on economic growth during the period 2000-2010. It has reached to find out that this effect was weak.